Salesforce.com - Davis, Justin (Teach yourself visually., 2013)
This visual guide shows you everything you need to know to get the most out of Salesforce.com. You'll discover how to organize contacts, log activities with contacts, schedule business appointments, use forecasting tools to predict upcoming sales, and make accurate projections based on past performance.